Perceptual asynchrony for motion - Lo, Yu Tung; Zeki, Semir (Frontiers in Human Neuroscience, 2014)
Psychophysical experiments show that two different visual attributes, colour and motion, processed in different areas of the visual brain, are perceived at different times relative to each other (Moutoussis and Zeki 1997a). Here we demonstrate psychophysically that two variants of the same attribute, motion, which have the same temporal structure and are processed in the same visual areas, are also processed asynchronously. When subjects were asked to pair up-down motion of dots in one half of their hemifield with up-right motion in the other, they perceived the two directions of motion asynchronously, with the advantage in favour of up-right motion; when they were asked to pair the motion of white dots moving against a black background with that of red dots moving against an equiluminant green background, they perceived the luminant motion first, thus demonstrating a perceptual advantage of luminant over equiluminant motion. These results were not affected by motion speed or perceived motion ‘streaks’. We thus interpret these results to reflect the different processing times produced by luminant and equiluminant motion stimuli or by different degrees of motion direction change, thus adding to the evidence that processing time within the visual system is a major determinant of perceptual time.